Early modern Jewry: a new cultural history - Ruderman, Daṿid (Princeton University Press, 2010)
Jews on the move -- Communal cohesion -- Knowledge explosion -- Crisis of rabbinic authority -- Mingled identities -- Toward modernity: some final thoughts